Halogen-doped lithium nickel cobalt aluminate and preparation method and application thereof
Through step-by-step mixing and multi-step heat treatment, combined with metal halides, the problems of uneven dispersion of aluminum atoms and incomplete halogen doping in nickel-cobalt aluminate are solved, and the preparation of halogen-doped nickel-cobalt aluminate with high specific capacity and good cycle performance is achieved.
Patent Information
- Application Number
- CN202311414511.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-10-27
AI Technical Summary
The preparation process of traditional nickel-cobalt lithium aluminate (NCA) is difficult to achieve uniform dispersion of aluminum atoms, resulting in poor electrochemical performance and difficult to effectively dopate halogen doping inside the lattice.
Halogen-doped lithium nickel-cobalt aluminate is prepared by controlling the mixing and heat treatment sequence of each metal source and introducing halogen through metal halides.
The uniform mixing of each element and the effective doping of halogen into the lattice are achieved, improving the specific capacity and cycling performance of the material.
Smart Images

Figure CN119905497A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of preparation of ternary materials for lithium-ion batteries, and in particular, to a halogen-doped lithium nickel cobalt aluminum oxide and a preparation method and application thereof. Background Art
[0002] Nickel cobalt aluminum oxide (NCA) is one of the most representative lithium battery ternary cathode materials and has been widely used in the field of new energy vehicles. However, its preparation process still faces certain challenges. The traditional co-precipitation preparation method makes it difficult to achieve uniform dispersion of aluminum atoms and easily leads to poor sphericity and loose structure, which in turn affects the electrochemical performance of the product. Therefore, improving the preparation process of NCA to achieve uniform dispersion of the three elements is expected to improve the electrochemical performance of the material and has strong practical value.
[0003] As the nickel content increases, the discharge capacity of NCA increases, but Ni 2+ With Li + More serious dislocation occurs (the two have similar ionic radii), resulting in significantly worse cycle performance and thermal stability. In order to reduce ion mixing, an effective method is bulk ion doping. Bulk ion doping can stabilize the layered structure, reduce the degree of cation mixing, and improve the structural stability of the material. Among them, halogen atom doping can partially replace O 2- , changing the valence state of transition metal ions, thereby changing the lattice structure parameters. Currently, the introduction of halogen atoms is mostly done by adding halogen-containing compounds during the lithiation and roasting stage, but this method easily causes halogen atoms to aggregate on the particle surface, making it difficult to achieve effective doping inside the lattice. Summary of the invention
[0004] The purpose of the present disclosure is to provide a halogen-doped lithium nickel cobalt aluminum oxide and a preparation method and application thereof. In order to achieve the above-mentioned purpose, the first aspect of the present disclosure provides a method for preparing halogen-doped lithium nickel cobalt aluminum oxide, the method comprising the following steps:
[0005] S1, performing a first solid phase mixing of nickel hydroxide and an aluminum source to obtain a first solid material;
[0006] S2, performing a second solid phase mixing of the first solid material and a cobalt source, and performing a first heat treatment on the obtained mixed material under a first oxygen-containing atmosphere to obtain a second solid material;
[0007] S3, performing a third solid phase mixing of the second solid material and a lithium source, and performing a second heat treatment on the obtained mixed material under a second oxygen-containing atmosphere;
[0008] The cobalt source and / or the aluminum source contains halogen.
[0009] Optionally, the aluminum source includes one or more of aluminum hydroxide, aluminum oxide, aluminum carbonate, aluminum oxalate, aluminum acetate, aluminum fluoride, aluminum chloride, aluminum bromide, and aluminum iodide;
[0010] The cobalt source includes one or more of cobalt hydroxide, cobalt oxide, cobalt carbonate, cobalt oxalate, cobalt acetate, cobalt fluoride, cobalt chloride, cobalt bromide, and cobalt iodide;
[0011] The lithium source includes one or more of lithium hydroxide, lithium carbonate, and lithium nitrate.
[0012] Optionally, the methods of the first solid-phase mixing, the second solid-phase mixing, and the third solid-phase mixing include solid-phase ball milling, and the times are 1-5 h respectively.
[0013] Optionally, in step S2, the method of the first heat treatment includes roasting, and the conditions of the first heat treatment include: the time is 2-8 h, and the temperature is 400-900 °C.
[0014] Optionally, in step S3, the method of the second heat treatment includes roasting, and the conditions of the second heat treatment include: the time is 10-20 h, and the temperature is 600-850 °C.
[0015] Optionally, the average particle size of the nickel hydroxide is 5-15 μm.
[0016] Optionally, the first oxygen-containing atmosphere and the second oxygen-containing atmosphere are respectively an oxygen atmosphere or an air atmosphere.
[0017] The second aspect of the present disclosure provides a halogen-doped lithium nickel cobalt aluminate prepared by using the method described in the first aspect of the present disclosure.
[0018] Optionally, the halogen-doped lithium nickel cobalt aluminate includes particles with the chemical formula LiNi 1-x-y Co x Al y O 2-0.5z X z , 0.6 ≤ 1 - x - y < 1, 0 < x ≤ 0.2, 0 < y ≤ 0.2, 0 < z ≤ 0.1, and X is one or more of F, Cl, Br, and I.
[0019] The third aspect of the present disclosure provides a lithium-ion battery, which includes a positive electrode, an electrolyte, and a negative electrode, and the positive electrode includes the halogen-doped lithium nickel cobalt aluminate described in the second aspect of the present disclosure.
[0020] Through the above technical scheme, the present application adopts a method of step-by-step mixing combined with multi-step heat treatment, controls the order of mixing and heat treatment of each metal source, and introduces halogens through metal halides to obtain halogen-doped lithium nickel cobalt aluminum oxide. The method disclosed in the present invention has simple steps, is conducive to industrial scale-up implementation and mass production, and the elements in the prepared halogen-doped lithium nickel cobalt aluminum oxide are relatively uniformly mixed, and at least part of the halogen can be doped into the interior of the lattice; it is used as a positive electrode material for lithium-ion batteries, and has a higher specific capacity and better cycle performance.
[0021] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0023] Figure 1 Electrochemical cycle curves of lithium nickel cobalt aluminum oxide A1, D1, and D2 prepared in Example 1 and Comparative Examples 1-2 of the present disclosure.
[0024] Figure 2 X-ray diffraction patterns of lithium nickel cobalt aluminum oxide A1, D1, and D2 prepared in Example 1 and Comparative Examples 1-2 of the present disclosure.
[0025] Figure 3 The scanning electron microscope image and element distribution map of F-doped nickel cobalt aluminum oxide A1 prepared in Example 1 of the present disclosure.
[0026] Figure 4 The scanning electron microscope image and element distribution map of F-doped nickel cobalt aluminum oxide D2 prepared in comparative example 2 of the present disclosure. DETAILED DESCRIPTION
[0027] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0028] The first aspect of the present disclosure provides a method for preparing halogen-doped lithium nickel cobalt aluminum oxide, the method comprising the following steps:
[0029] S1, performing a first solid phase mixing of nickel hydroxide and an aluminum source to obtain a first solid material;
[0030] S2, performing a second solid phase mixing of the first solid material and a cobalt source, and performing a first heat treatment on the obtained mixed material under a first oxygen-containing atmosphere to obtain a second solid material;
[0031] S3, performing a third solid phase mixing of the second solid material and a lithium source, and performing a second heat treatment on the obtained mixed material under a second oxygen-containing atmosphere;
[0032] The cobalt source and / or the aluminum source contains halogen.
[0033] The present application adopts a method of step-by-step mixing combined with multi-step heat treatment, controls the order of mixing and heat treatment of each metal source, and introduces halogen through metal halide to prepare halogen-doped nickel cobalt aluminum oxide. The method disclosed in the present invention utilizes the migration of cobalt atoms to drive the migration of other atoms, which can not only achieve the proportion control and uniform mixing of each element, but also achieve the effective doping of halogen atoms and broaden their sources. The elements in the prepared halogen-doped nickel cobalt aluminum oxide are relatively uniformly mixed, and at least part of the halogen can be doped into the bulk phase of the material and can be doped into the interior of the crystal lattice. It is used as a positive electrode material for lithium-ion batteries, and has a higher specific capacity and better cycle performance.
[0034] According to an embodiment of the present disclosure, the halogen includes one or more of fluorine, chlorine, bromine and iodine.
[0035] According to one embodiment of the present disclosure, the nickel hydroxide has a spherical and / or quasi-spherical morphology, and the spherical and quasi-spherical shapes are both conventionally defined in the art. Preferably, the average particle size of the nickel hydroxide is 5-15 μm.
[0036] According to one embodiment of the present disclosure, in order to achieve uniform mixing, the first solid phase mixing, the second solid phase mixing and the third solid phase mixing include solid phase ball milling for 1-5 hours, preferably 2-4 hours; solid phase ball milling can be performed on a planetary ball mill, for example.
[0037] According to one embodiment of the present disclosure, the types of aluminum source, cobalt source and lithium source are conventional in the art. For example, the aluminum source includes one or more of aluminum hydroxide, aluminum oxide, aluminum carbonate, aluminum oxalate, aluminum acetate, aluminum fluoride, aluminum chloride, aluminum bromide and aluminum iodide. When the aluminum source includes more than two substances, there is no specific restriction on their proportion; the cobalt source includes one or more of cobalt hydroxide, cobalt oxide, cobalt carbonate, cobalt oxalate, cobalt acetate, cobalt fluoride, cobalt chloride, cobalt bromide and cobalt iodide. When the cobalt source includes more than two substances, there is no specific restriction on their proportion; the lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate. When the lithium source includes more than two substances, there is no specific restriction on their proportion.
[0038] In the present disclosure, the lithium source does not contain halogen.
[0039] According to an embodiment of the present disclosure, in step S2, the first heat treatment method includes roasting, and the conditions of the first heat treatment include: the time is 2 - 8 h, and the temperature is 400 - 900 °C; preferably, the time is 3 - 7 h, and the temperature is 500 - 800 °C; these conditions can exert the migration effect of metal ions and promote the uniform dispersion of each element.
[0040] According to an embodiment of the present disclosure, in step S3, the second heat treatment method includes roasting, and the conditions of the second heat treatment include: the time is 10 - 20 h, and the temperature is 600 - 850 °C; preferably, the time is 12 - 18 h, and the temperature is 700 - 800 °C; under these conditions, the diffusion of Li is better, and a higher material capacity can be obtained.
[0041] According to an embodiment of the present disclosure, the first oxygen-containing atmosphere and the second oxygen-containing atmosphere are respectively an oxygen atmosphere or an air atmosphere, wherein the definitions of the oxygen-containing atmosphere and the air atmosphere are conventional in the art.
[0042] In the present disclosure, the roasting method is conventional in the art, for example, it can be carried out in a sagger.
[0043] In the present disclosure, some halogens may be lost during the preparation process.
[0044] In the present disclosure, the dosages of nickel hydroxide, cobalt source, and aluminum source are set according to the molar ratios of nickel element, cobalt element, and aluminum element in the product.
[0045] According to an embodiment of the present disclosure, the molar ratio of the lithium source calculated by lithium element to the second solid material calculated by the total amount of nickel element, cobalt element, and aluminum element can be, for example, (0.8 - 1.2):1, preferably (0.95 - 1.15):1, and some lithium sources may be lost during ball milling and heat treatment.
[0046] The second aspect of the present disclosure provides a halogen-doped lithium nickel cobalt aluminate prepared by using the method described in the first aspect of the present disclosure.
[0047] According to an embodiment of the present disclosure, the halogen-doped lithium nickel cobalt aluminate includes particles with the chemical formula LiNi 1-x- y Co x Al y O 2-0.5z X z , where 0.6 ≤ 1 - x - y < 1, 0 < x ≤ 0.2, 0 < y ≤ 0.2, 0 < z ≤ 0.1, and X is one or more of F, Cl, Br, and I; preferably, 0.7 ≤ 1 - x - y ≤ 0.96, 0.02 ≤ x ≤ 0.15, 0.02 ≤ y ≤ 0.15, 0 < z ≤ 0.05.
[0048] A third aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the halogen-doped lithium nickel cobalt aluminum oxide described in the second aspect of the present disclosure.
[0049] According to one embodiment of the present disclosure, the negative electrode is conventional in the art, and for example may include one or more of a lithium sheet, a carbon material, and a silicon-carbon composite material.
[0050] According to one embodiment of the present disclosure, the electrolyte is conventional in the art, for example, may include one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, lithium hexafluorophosphate and dimethyl carbonate.
[0051] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form.
[0052] The raw materials used in the examples were all purchased from commercial sources and were of analytical grade unless otherwise specified.
[0053] The testing instrument model of the scanning electron microscope SEM is FEIQUANTA400, and the method is that the acceleration voltage is 20 kV;
[0054] The X-ray diffraction pattern XRD test instrument model is the X-ray powder diffractometer of Philips Company of the United States. The method is to use Cu target anode Kα radiation source, step width of 0.02°, scanning speed of 2° / min, 2θ=10°-80°.
[0055] The testing instrument model of X-ray photoelectron spectroscopy XPS is ESCALAB 250.
[0056] Testing method for the chemical formula of positive electrode materials: Inductively coupled plasma mass spectrometry.
[0057] Example 1
[0058] Fluorine-doped lithium nickel cobalt aluminum oxide A1 was prepared by the following steps:
[0059] (1) According to the molar ratio of n(Ni):n(Al)=0.9:0.03, 0.9 mol of spherical nickel hydroxide (average particle size of 8.5 μm), 0.02 mol of aluminum hydroxide and 0.01 mol of aluminum fluoride were weighed respectively, and mixed for 2 hours on a planetary ball mill to obtain a first solid material;
[0060] (2) according to the molar ratio of n(Ni):n(Co)=0.9:0.07, 0.07 mol of cobalt acetate was weighed and added to the first solid material, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 700° C. for 5 hours to obtain a second solid material;
[0061] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, 1.05 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 730°C for 15 h. The obtained solid product was crushed and sieved to obtain fluorine-doped nickel cobalt aluminum oxide A1 with a chemical formula of LiNi 0.9 Co 0.07 Al 0.03 O 1.9895 F 0.021 , the parameters are listed in Table 1.
[0062] Example 2
[0063] The chlorine-doped lithium nickel cobalt aluminum oxide A2 was prepared by the following steps:
[0064] (1) According to the molar ratio of n(Ni):n(Al)=0.8:0.05, 0.8 mol of spherical nickel hydroxide (average particle size of 8.2 μm) and 0.05 mol of aluminum hydroxide powder were weighed respectively, and mixed on a planetary ball mill for 2 hours to obtain a first solid material;
[0065] (2) According to the molar ratio of n(Ni):n(Co)=0.8:0.15, 0.135 mol of cobalt acetate and 0.015 mol of cobalt chloride were weighed and added to the first solid material, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 600° C. for 6 h to obtain a second solid material;
[0066] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, 1.05 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 3 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 750°C for 18 h. The obtained solid product was crushed and sieved to obtain chlorine-doped nickel cobalt aluminum lithium A2, with a chemical formula of LiNi 0.8 Co 0.15 Al 0.05 O 1.992 Cl 0.016 .
[0067] Example 3
[0068] The bromine-doped lithium nickel cobalt aluminum oxide positive electrode material A3 was prepared by the following steps:
[0069] (1) According to the molar ratio of n(Ni):n(Al)=0.89:0.03, 0.89 mol of spherical nickel hydroxide (average particle size of 8.5 μm) and 0.03 mol of aluminum oxide powder were weighed respectively, and mixed for 2 hours on a planetary ball mill to obtain a first solid material;
[0070] (2) According to the molar ratio of n(Ni):n(Co)=0.89:0.08, 0.07 mol of cobalt carbonate and 0.01 mol of cobalt bromide were weighed and added to the first solid material, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 700° C. for 5 h to obtain a second solid material;
[0071] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.06:1, 1.06 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, and after mixing for 3 hours on a planetary ball mill, the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 710°C for 18 hours. The obtained solid product was crushed and sieved to obtain bromine-doped lithium nickel cobalt aluminum oxide A3, with a chemical formula of LiNi 0.89 Co 0.08 Al 0.03 O 1.9951 Br 0.0098 .
[0072] Example 4
[0073] The iodine-doped lithium nickel cobalt aluminum oxide A4 was prepared by the following steps:
[0074] (1) According to the molar ratio of n(Ni):n(Al)=0.92:0.03, 0.92 mol of spherical nickel hydroxide (average particle size of 8.5 μm), 0.02 mol of aluminum hydroxide and 0.01 mol of aluminum iodide were weighed respectively, and mixed for 2 hours on a planetary ball mill to obtain a first solid material;
[0075] (2) according to the molar ratio of n(Ni):n(Co)=0.92:0.05, 0.05 mol of cobalt acetate was weighed and added to the first solid material, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 800° C. for 6 hours to obtain a second solid material;
[0076] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.08:1, 1.08 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, and after mixing for 3 hours on a planetary ball mill, the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 720°C for 18 hours. The obtained solid product was crushed and sieved to obtain iodine-doped nickel cobalt aluminum lithium A4, with a chemical formula of LiNi 0.92 Co 0.05 Al 0.03 O 1.994 I 0.012 .
[0077] Comparative Example 1
[0078] The fluorine-doped lithium nickel cobalt aluminum oxide D1 was prepared by the following steps:
[0079] (1) According to the molar ratio of n(Ni):n(Al)=0.9:0.03, 0.9 mol of spherical nickel hydroxide (average particle size of 8.5 μm) and 0.03 mol of aluminum hydroxide were weighed respectively, and mixed on a planetary ball mill for 2 hours to obtain a first solid material;
[0080] (2) According to the molar ratio of n(Ni):n(Co)=0.9:0.07, 0.07 mol of cobalt acetate and 0.03 mol of ammonium fluoride were weighed and added to the first solid material, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 700° C. for 5 h to obtain a second solid material;
[0081] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, 1.05 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 730°C for 15 h. The obtained solid product was crushed and sieved to obtain a fluorine-doped nickel cobalt aluminum oxide lithium positive electrode material D1 with a chemical formula of LiNi 0.9 Co 0.07 Al 0.03 O 1.992 F 0.016 , the parameters are listed in Table 1.
[0082] Comparative Example 2
[0083] The fluorine-doped lithium nickel cobalt aluminum oxide D2 was prepared by the following steps:
[0084] (1) According to the molar ratio of n(Ni):n(Al)=0.9:0.03, 0.9 mol of spherical nickel hydroxide (average particle size of 8.5 μm) and 0.03 mol of aluminum hydroxide were weighed respectively, and mixed on a planetary ball mill for 2 hours to obtain a first solid material;
[0085] (2) according to the molar ratio of n(Ni):n(Co)=0.9:0.07, 0.07 mol of cobalt acetate was weighed and added to the first solid material, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 700° C. for 5 hours to obtain a second solid material;
[0086] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, 1.02 mol of lithium hydroxide, 0.03 mol of lithium fluoride and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 730°C for 15 h. The obtained solid product was crushed and sieved to obtain fluorine-doped lithium nickel cobalt aluminum oxide D2 with a chemical formula of LiNi 0.9 Co 0.07 Al 0.03 O 1.989 F 0.022 , the parameters are listed in Table 1.
[0087] Table 1
[0088] Material No. Unit cell parameter c(nm) Atomic ratio of surface F element (%) Example 1 A1 1.42275 1.64 Comparative Example 1 D1 1.42263 1.96 Comparative Example 2 D2 1.42269 2.53
[0089] The unit cell parameters in Table 1 were tested by XRD, and the “atomic ratio of the surface F element” refers to the ratio of F atoms on the particle surface to all atoms on the surface, which was tested by XPS.
[0090] According to the data in Table 1, compared with D1-D2, the unit cell parameter of the halogen-doped nickel cobalt aluminum oxide A1 prepared by the method disclosed in the present invention is larger, which is conducive to the transmission of lithium ions; when the amount of F is the same, the atomic ratio of the F element on the surface of A1 is relatively low, indicating that the F element is doped into the interior of the material.
[0091] XRD test was performed on A1, D1 and D2, and the results are as follows: Figure 2 shown.
[0092] according to Figure 2 It can be seen that when the amount of F is the same, the peak position of A1 is more offset than that of material D1 in which halogen is introduced through ammonium fluoride and material D2 doped with surface halogen, indicating that the doping degree of F element is higher and at least part of the halogen is doped into the crystal lattice of the material.
[0093] The scanning electron microscope (SEM) test was performed on samples A1 and D2 to analyze the element distribution of the samples. The results are as follows: Figure 3 and Figure 4 shown.
[0094] according to Figure 3 and Figure 4 It can be seen that compared with D2, the four elements Ni, Co, Al, and F in A1 are evenly dispersed, indicating that the elements in the halogen-doped lithium nickel cobalt aluminum oxide prepared by the method disclosed in the present invention are evenly distributed.
[0095] Test Case
[0096] The electrochemical performance test of the nickel cobalt aluminum oxide lithium A1 and D1-D2 prepared in the embodiment and the comparative example was carried out, and the specific steps were as follows:
[0097] The positive electrode material, conductive agent (acetylene black), and binder (polyvinylidene fluoride) were weighed in a mass ratio of 8:1:1 and mixed evenly with the solvent (N-methylpyrrolidone), coated on aluminum foil and cut into sheets as the positive electrode; then mixed with lithium sheet, electrolyte (1 mol·L -1 LiPF6 ethylene carbonate / ethyl methyl carbonate / dimethyl carbonate solution, mass ratio of 1:1:1) and a separator (Celgard2300) were used to form a lithium ion half-cell, and the electrochemical performance test results are as follows Figure 1 shown.
[0098] Specific test conditions: the charge and discharge voltage range is 2.75-4.3V; the charge and discharge rate is 0.1C for the first 4 times and 0.5C after the 5th time; the test temperature is 35℃.
[0099] according to Figure 1 It can be seen that after 200 cycles, the discharge specific capacity of sample D1 introduced with ammonium fluoride pre-burning is 148.3 mAh / g, and the capacity retention rate is 76.44%; the discharge specific capacity of sample D2 introduced with LiF in the lithiation stage is 153.6 mAh / g, and the capacity retention rate is 80.74%; the discharge specific capacity of fluorine-doped nickel cobalt aluminum oxide A1 prepared by the method disclosed in the present invention is 165.0 mAh / g, and the capacity retention rate is 86.04%.
[0100] According to the above data, the elements in the halogen-doped nickel cobalt aluminum oxide prepared by the method disclosed in the present invention are mixed relatively evenly, and at least part of the halogen can be doped into the interior of the crystal lattice; when used as a positive electrode material for a lithium-ion battery, it has a higher specific capacity and better cycle performance.
[0101] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments; within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0102] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0103] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing halogen-doped lithium nickel cobalt aluminum oxide, characterized in that: The method comprises the following steps: S1, performing a first solid phase mixing of nickel hydroxide and an aluminum source to obtain a first solid material; S2, performing a second solid phase mixing of the first solid material and a cobalt source, and performing a first heat treatment on the obtained mixed material under a first oxygen-containing atmosphere to obtain a second solid material; S3, performing a third solid phase mixing of the second solid material and a lithium source, and performing a second heat treatment on the obtained mixed material under a second oxygen-containing atmosphere; The cobalt source and / or the aluminum source contains halogen.
2. The method according to claim 1, wherein: The aluminum source includes one or more of aluminum hydroxide, aluminum oxide, aluminum carbonate, aluminum oxalate, aluminum acetate, aluminum fluoride, aluminum chloride, aluminum bromide and aluminum iodide; The cobalt source includes one or more of cobalt hydroxide, cobalt oxide, cobalt carbonate, cobalt oxalate, cobalt acetate, cobalt fluoride, cobalt chloride, cobalt bromide and cobalt iodide; The lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate.
3. The method according to claim 1, wherein: The first solid phase mixing, the second solid phase mixing and the third solid phase mixing include solid phase ball milling, and the time is 1-5 hours respectively.
4. The method according to claim 1, wherein: In step S2, the first heat treatment method includes calcination, and the conditions of the first heat treatment include: time of 2-8h and temperature of 400-900°C.
5. The method according to claim 1, wherein: In step S3, the second heat treatment method includes roasting, and the conditions of the second heat treatment include: time is 10-20h, and temperature is 600-850°C.
6. The method according to claim 1, wherein: The average particle size of the nickel hydroxide is 5-15 μm.
7. The method according to claim 1, wherein: The first oxygen-containing atmosphere and the second oxygen-containing atmosphere are respectively an oxygen atmosphere or an air atmosphere.
8. Halogen-doped lithium nickel cobalt aluminum oxide prepared by the method according to any one of claims 1 to 7.
9. The halogen-doped lithium nickel cobalt aluminum oxide according to claim 8, wherein: The halogen-doped lithium nickel cobalt aluminate includes particles with the chemical formula LiNi 1-x-y Co x Al y O 2-0.5z X z , where 0.6 ≤ 1 - x - y < 1, 0 < x ≤ 0.2, 0 < y ≤ 0.2, 0 < z ≤ 0.1, and X is one or more of F, Cl, Br, and I.
10. A lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode comprises the halogen-doped lithium nickel cobalt aluminum oxide as claimed in claim 8 or 9.
Citation Information
Patent Citations
Method for preparing lithium nickel cobalt aluminum oxides serving as lithium ion battery positive electrode material
CN102173465A
High-density lithium ion battery anode material nickel-cobalt lithium aluminate and preparation method thereof
CN103050686A
Oxygen doped nickel-cobalt-aluminum cathode material and preparation method thereof and application of oxygen doped nickel-cobalt-aluminum cathode material
CN109860563A